Garbage can theory and Australia's National Electricity Market: Decarbonisation in a hostile policy environment. (September 2018) - Simshauser, Paul
Abstract: After two decades of consistent economic and technical performance, conditions in Australia's National Electricity Market (NEM) deteriorated sharply in 2016/17. Prices more than doubled on the east coast, tripled in South Australia (SA), and the SA regional grid collapsed. Nothing spectacular occurred with final demand – this was a supply-side energy crisis driven by the exit of 18% of Australia's coal-fired generation fleet and the inadequate entry of new plant. Australia's NEM encountered an uncoordinated exit-driven episode of the Resource Adequacy problem. In the USA where 18% of coal plant has also exited, Resource Adequacy and low cost energy has been maintained by the entry of an enormous fleet of wind, solar and gas-fired generators. In Australia, an equivalent response did not occur; decades of climate change policy discontinuity meant the speed of coal plant exit was unpredictable, entry of renewables delayed through stop-start policy, and gas-fired plant was subject to critical hold-up due to excess LNG plant investment. Resolution requires a united and stable climate change policy architecture that works with, not against, the NEM's world-class institutional design, and greater transparency around planned plant exit. Highlights: Conditions in Australia's NEM deteriorated in 2016/17. Coal plant is exiting, but entry of renewables has been delayed. This follows two decades of climate change policy uncertainty. Gas plant entry has been distorted due to gas market failures.